Motor asynchrony in students with high abilities/giftedness and twice exceptionality: Identification and holistic interventions in the school environment: Scoping review: Motor asynchrony in gifted and twice-exceptional students - Henrique Lopes, Fernando; R. Afonso, João Pedro; F. Sudré, Tamyris M.; Alves, Gabriel I. C.; Pires, Luis Felipe M.; Amorim, Simone C. D.; Oliveira, Jordão R.; Andrade, Lucas S.; Oliveira-Silva, Iransé (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
Background: The education of students with Giftedness/High Abilities (G/HA) and Twice Exceptionality (2e) represents a challenge in the Brazilian context, especially due to the phenomenon of motor asynchrony. This condition, characterized by a mismatch between advanced cognitive development and fine and gross motor skills, manifests as graphomotor difficulties, poor coordination, and low body confidence. Despite the legal framework guaranteeing educational rights for this population, there is a significant gap between legislation and effective identification and intervention practices in the school environment. Objectives: This scoping review aimed to map and analyze the scientific literature on motor asynchrony in students with G/HA and 2e, as well as to identify psychomotor, pedagogical, and socio-emotional intervention strategies applied in school settings between 2008 and 2025. Methods: The research followed the PRISMA-ScR protocol, covering thirteen national and international databases (PubMed, LILACS, ERIC, Scopus, Web of Science, SciELO, among others). The search yielded 192 initial records, of which 16 articles met the inclusion criteria after screening. Data analysis was based on thematic categorization, yielding three main themes: identification of motor asynchrony, student characteristics, and intervention strategies. Conclusions: The analysis revealed that motor asynchrony is an intrinsic manifestation of the development of students with G/HA and 2e, impacting their academic expression, self-image, and engagement. The most effective interventions were holistic and interdisciplinary, integrating psychomotricity, inclusive physical education, occupational therapy, differentiated teaching strategies, and emotional support. The study proposes an Inclusive Educational Model for Body-Cognition Integration (MEICC) with seven interconnected components, aiming to overcome the mind-body fragmentation and promote the holistic development of these students. It is concluded that integrating the body as a dimension of intelligence is essential to reduce underachievement and broaden the participation and well-being of these students in the school environment.